'Formation' of the female author in the hip hop visual album: Beyoncé and FKA twigs. Issue 1 (1st December 2016) - Barrett, Ciara
This article explores how and why, from a feminist standpoint, two black female hip hop artists – Beyoncé and FKA twigs – have turned in recent years to the emerging audio-visual format of the visual album towards a radical expression of female authorship. This is 'radical', specifically, in two contexts: firstly hip hop, the genre with which these artists are traditionally associated and which has been associated, historically, with a repressive politics of gender and race representation through music videos and secondly, that of the classical paradigm of film style and narration, which the visual album as long-form video implicitly confronts. Synthesizing traditional feminist film theory with more recent theorization of music video aesthetics and representational trends, this article considers how Beyoncé and FKA twigs have remediated certain formal and narrative paradigms of film and music video to create a uniquely hybrid form. Beyoncé's self-titled visual album from 2013 will be considered as an initial interrogation-cum-problematization of the sexist representational paradigms endemic to hip hop music videos and classical cinema from the inside out, while her more recent Lemonade and twigs's M3ll155X will be analysed as radically formally innovative and assertive of a subjective, female authorial voice. These two artists will be seen to have self-consciously invoked a filmic mode of representation and spectatorship across the formally experimental audio-visual format of the video album to exert a remarkable degree of control over their audio-self-images' narrativization and signification.